Immobilized titanium dioxide for emerging contaminant removal in wastewater - Yasmine, Abdel-Maksoud (AUC Knowledge Fountain, 2018)
There have been rising concerns about emerging contaminants that are not efficiently removed by conventional wastewater treatment plants. TiO2 photocatalysis is one of the promising routes for sustainable wastewater treatment. Research on the use of TiO2 photocatalysis for water/wastewater treatment for the removal of persistent non-biodegradable emerging water pollutant is active worldwide. Since the mid-1970s the viability of photocatalytic degradation of organic compounds in water using TiO2 was demonstrated. More than 1,000 substances have been degraded using TiO2. Despite the extensive research on photocatalytic oxidation using TiO2, pilot and demonstration plants through the last four decades are still countable. Widespread use of photocatalytic treatment of water and wastewater require the development of an innovative photocatalytic reactor that is efficient, reliable, simple to construct, easy to maintain, has low energy consumption, low capital and operating cost and provides easy separation of catalyst after treatment ends. In an attempt to develop this desired photo-reactor, three photo-reactors were designed and constructed: the slurry water-bell photo-reactor, the immobilized water-bell photo-reactor and the immobilized tray photo-reactor. The slurry water-bell photo-reactor is based on generating a thin water film to allow for solar light penetration for photo-catalyst activation and continuous oxygenation. Recirculating the reaction solution at a high flow rate ensures good mixing and avoids dead zones in the photo-reactor. the reactor performance for degradation of phenol, as a model compound, was evaluated using commercial TiO2. Factors affecting the degradation efficiency were studied including catalyst loading, light intensity, initial pollutant concentration, oxidant addition and exposure time. Dissolved oxygen levels, temperature and pH were monitored through all the conducted tests. The performance of the slurry water-bell was compared with other photo-reactors using two benchmarks: the degradation rate constant and the reactor throughput. The reactor throughput is a function of the treated volume, treatment duration and reactor area footprint, thus it is as a versatile indicator for comparison between reactors of different types and geometries as well as selection of reactor configurations suitable for scale-up and commercialization. TiO2 was immobilized on sand grains for use as dispersed photo-catalyst in the water-bell reactor. Immobilization of TiO2 was conducted by two methods; direct immobilization using sol-gel synthesis and binding with epoxy coating. Photo-catalyst abrasion was encountered. The strong mixing conditions and flow through the recirculating pump resulted in high abrasion of the photo-catalyst off the sand surface. The tray photo-reactor was developed to avoid the high friction of the photo-catalyst particles in the recirculating pump while maintain fulfilling all the other photocatalytic process requirements of light penetration, continuous oxygen supply, and turbulent flow. The immobilized tray photocatalytic reactor uses a fixed-bed of TiO2 supported on sand grains. The reactor maintains a thin water film over the supported TiO2 catalytic bed. TiO2 was immobilized on the sand grains using 3 different immobilization approaches: 1) direct immobilization using the sol gel technique, 2) coating with TiO2/cement grout; and (3) binding with TiO2-epoxy coating. Reactor performance for the degradation of phenol as a model compound was evaluated for the three photo-catalysts. Immobilization of TiO2 on sand particles using epoxy was successful in achieving the highest phenol degradation and resistance to abrasion. The water turbidity remained unchanged indicating photo-catalyst resistance to abrasion even after multiple use of the catalytic bed. Successful operation of the tray photo-reactor in the continuous mode was also achieved. The performance of the immobilized tray photo-reactor was compared with other photo-reactors using three benchmarks: the initial degradation rate, the reactor throughput and turbidity. The immobilized tray photo-reactor is suitable for scale-up and commercialization due to five distinctive features which are: modular design; integrated storage; passive oxygenation; absence of need for UV transmitting components that are susceptible to breakage and optical losses, and simple and cheap components.